Long-term fine particular exposure and incidence of frailty in older adults: findings from the Chinese Longitudinal Healthy Longevity Survey. (14th February 2023) - Lv, Yuebin; Yang, Ze; Ye, Lihong; Jiang, Meijie; Zhou, Jinhui; Guo, Yanbo; Qiu, Yidan; Li, Xinwei; Chen, Chen; Ju, Aipeng; Wang, Jun; Li, Chenfeng; et al.
Abstract: Background: The association between fine particular matter (PM2.5 ) and frailty is less studied, and the national burden of PM2.5 -related frailty in China is unknown. Objective: To explore the association between PM2.5 exposure and incident frailty in older adults, and estimate the corresponding disease burden. Design: Chinese Longitudinal Healthy Longevity Survey from 1998 to 2014. Setting: Twenty-three provinces in China. Subjects: A total of 25, 047 participants aged ≥65-year-old. Methods: Cox proportional hazards models were performed to evaluate the association between PM2.5 and frailty in older adults. A method adapted from the Global Burden of Disease Study was used to calculate the PM2.5 -related frailty disease burden. Results: A total of 5, 733 incidents of frailty were observed during 107, 814.8 person-years follow-up. A 10 μg/m 3 increment of PM2.5 was associated with a 5.0% increase in the risk of frailty (Hazard Ratio = 1.05, 95% confidence interval = [1.03–1.07]). Monotonic, but non-linear exposure-response, relationships of PM2.5 with risk of frailty were observed, and slopes were steeper at concentrations >50 μg/m³. Considering the interaction between population ageing and mitigation of PM2.5, the PM2.5 -related frailty cases were almost unchanged in 2010, 2020 and 2030, with estimations of 664, 097, 730, 858 and 665, 169, respectively. Conclusions: This nation-wide prospective cohort study showed a positive association between long-term PM2.5 exposure and frailty incidence. The estimated disease burden indicated that implementing clean air actions may prevent frailty and substantially offset the burden of population ageing worldwide.